Analisis Pelaksanaan Program PIS-PK Terhadap Indikator Pengobatan Teratur Penderita Hipertensi di Wilayah Kerja Puskesmas Kuala Tungkal II Tahun 2025 - Ermawaty Karo-karo; Nina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Healthy Indonesia Program with Family Approach (PIS-PK) is a national strategy to improve public health through family-based interventions. A crucial problem in this program is hypertension patients' adherence to regular treatment. In the working area of Puskesmas Kuala Tungkal II, the achievement of this indicator was only 38.77% in 2024, far from the 100% national target. This study aims to analyze the implementation of the PIS-PK Program on the regular treatment indicator for hypertension patients based on input, process, and output aspects. This study applied a qualitative approach with a phenomenological design. The informants included the head of the community health center, program managers, implementing doctors, and ten purposively selected hypertension patients. Data were collected through in-depth interviews, observations, and document reviews. The results indicate that although health services are accessible, obstacles such as distance and transportation dependency persist. Posbindu PTM is available but not entirely active, and health education remains unstructured. Furthermore, the medication adherence monitoring system, physical activity promotion, and smoking cessation counseling have not functioned optimally due to limited manpower, funds, and facilities. In conclusion, the PIS-PK implementation is not yet optimal. Strengthening education, cadre training, and continuous monitoring are highly required to improve hypertension patients' medication adherence.